1984
DOI: 10.1111/j.1365-2265.1984.tb03456.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Effect of Antithyroid Drugs on the Natural History of Graves' Disease

Abstract: In the United Kingdom, about half the patients with Graves' disease who are given antithyroid drugs are still in remission one year after treatment is stopped. The most widely held view is that such remission rates are due only to the biochemical effects of the drugs, the disease either spontaneously remitting or abating when the immune system is no longer subject to the stimulatory effects of excessive thyroid hormone. We review here the accumulating evidence against both of these alternatives. In contrast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(73 citation statements)
references
References 49 publications
2
69
0
2
Order By: Relevance
“…The decrease in thymic size and density by treatment with antithyroid drugs could be produced, at least in part, by an indirect action by lowering circulating thyroid hormone levels, since it has been reported that exogenous thyroid hormone administration to experimental animals resulted in enlargement of both cortical and medullary components of the thymus (29,30), while thyroidectomy induced a reduction of thymic size (31). It has also been suggested that antithyroid drugs not only cause a block of thyroid hormone synthesis, but also have immunosuppressive effects, including lowering TSHreceptor antibody levels (32). Thus, antithyroid drugs might also induce thymic atrophy by mechanisms related to their immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in thymic size and density by treatment with antithyroid drugs could be produced, at least in part, by an indirect action by lowering circulating thyroid hormone levels, since it has been reported that exogenous thyroid hormone administration to experimental animals resulted in enlargement of both cortical and medullary components of the thymus (29,30), while thyroidectomy induced a reduction of thymic size (31). It has also been suggested that antithyroid drugs not only cause a block of thyroid hormone synthesis, but also have immunosuppressive effects, including lowering TSHreceptor antibody levels (32). Thus, antithyroid drugs might also induce thymic atrophy by mechanisms related to their immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the significant decrease in serum CXCL10 after restoration of euthyroidism in GD patients reported here could be reasonably ascribed to the well-known immunomodulatory effect of antithyroid drugs. In fact, besides its ability to decrease thyroid hormone production (28), MMI appears to interfere with the immunologic abnormalities in GD hyperthyroidism, as shown by the 50% of patients successfully cured by the drug and by the significant decrease of serum antithyroid antibodies observed in most treated patients (28,29). Therefore, these drugs may have influenced chemokine levels, especially as the same drugs can reduce cytokine expression by TFC with a final effect of reducing infiltration into the gland (30).…”
Section: Discussionmentioning
confidence: 99%
“…MMI, besides its ability to decrease thyroid hormone production (138), has been shown to interfere with some immunological abnormalities typical of Graves' hyperthyroidism. The immunosuppressive effect of MMI is highlighted by the reduction of circulating thyroid antibodies, which occurs during medical treatment with this drug, and by the consistent percentage (nearly 30%) of Graves' patients entering prolonged remission after a course of medical therapy (138,139). These immunological effects of MMI might be mediated, at least in part, by an action on chemokine production, resulting in a decreased lymphocytic infiltration of the gland.…”
Section: Cxcr3-binding Chemokines In Graves' Diseasementioning
confidence: 99%